Rumen kambing sebagai bahan baku barang kulit - Lutfi, Muchtar (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The objective of this research is to identify the physical strength of crust of goat rumen to decide their benefit. Materials used in this study were 8 pieces of salted goat rumens which were then tanned to crust leather using chromosal B, and Irgatan LV. as tanning and retaning material. The crust leather, then, were tested on their strength and flexibility at Laboratory of leather and leather product quality control and normalization IRDLAI and the result showed that the tensile strength was low of (on average) 29,84 Kg./Cm2, while the flexibility (on average) was 103,13%. Viewed from the test result, the skins were still possible to be prepared as a kind of leather, or the skins were used as car whell sterring cover.Â Â INTISARIÂ Penelitian ini bertujuan untuk mengetahui kekuatan fisis kulit kras dari rumen kambing agar dapat ditentukan pemanfaatannya. Dengan menggunakan 8 buah rumen kambing awet garaman disamak menjadi kulit kras dengan menggunakan Chromosal B. sebagai bahan penyamak dan Irgatan LV. sebagai bahan penyamak ulangnya. Kulit kras hasil penelitian ini diujikan kekuatan tarik dan kemulurannya di Laboratorium PMNK. Balai Pengembangan Barang Kulit, dan didapatkan hasil kekuatan tarik yang rendah yaitu sebesar (rata-rata) 29,84 Kg./Cm2. sedangkan kemulurannya (rata-rata) 103,13%. Dilihat dari hasil uji tersebut, kulit dari rumen kambing masih memungkinkan dimanfaatkan untuk pengolahan sejenis dompet atau tas untuk wanita dengan cara dilapisi dengan kulit yang lain, atau dimanfaatkan untuk pembungkus stir mobil.